Analysis as history, and history as analysis: a search for common goals and standards. Issue 5 (29th July 2017) - Warner, Michael
Abstract: History is something far from storytelling about the past; it has its own methods, discipline, techniques, and value. The same can be said about intelligence analysis, which is a comparative newcomer to the professions. Like historians, analysts seek to gather information, evaluate their sources, create meaning from disparate bits of evidence, and impart significant findings. These considerations make it important for analysts to learn their history and how the discipline of history functions. A greater 'historical sense' can make analysts more rigorous in their work, and less likely to be frustrated by the situations they see around them.